2013
DOI: 10.1371/journal.pone.0055076
|View full text |Cite|
|
Sign up to set email alerts
|

Systematic Functional Comparative Analysis of Four Single-Stranded DNA-Binding Proteins and Their Affection on Viral RNA Metabolism

Abstract: The accumulation of single-stranded DNA-binding (SSB) proteins is essential for organisms and has various applications. However, no study has simultaneously and systematically compared the characteristics of SSB proteins. In addition, SSB proteins may bind RNA and play an unknown biological role in RNA metabolism. Here, we expressed a novel species of SSB protein derived from Thermococcus kodakarensis KOD1 (KOD), as well as SSB proteins from Thermus thermophilus (TTH), Escherichia coli, and Sulfolobus Solfatar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…In addition to protecting ssDNA from degradation, the high affinity of SSBs has also been exploited by nature to detect DNA damage ( 2 , 5 8 ), melt dsDNA ( 5 7 ) and to recruit other proteins to ssDNA stimulating their biochemical activity and the overall efficiency of DNA processing pathways ( 9 12 ). The vital roles of SSBs in genome maintenance and cell survival are reflected in their universal expression throughout all kingdoms of life ( 3 , 13 15 ), as well as their inclusion in some viral proteomes ( 15 ). In recent years, there has been also an increasing interest in the biotechnological potential of SSBs ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to protecting ssDNA from degradation, the high affinity of SSBs has also been exploited by nature to detect DNA damage ( 2 , 5 8 ), melt dsDNA ( 5 7 ) and to recruit other proteins to ssDNA stimulating their biochemical activity and the overall efficiency of DNA processing pathways ( 9 12 ). The vital roles of SSBs in genome maintenance and cell survival are reflected in their universal expression throughout all kingdoms of life ( 3 , 13 15 ), as well as their inclusion in some viral proteomes ( 15 ). In recent years, there has been also an increasing interest in the biotechnological potential of SSBs ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…In Eco SSB each monomer encodes for a single OB-fold, but exceptions to this arrangement include SSBs composed of two OB-folds per monomer and acting as homodimers in Deinococcus-thermus genera ( 28 ). Outside of the bacteria, SSBs exhibit quaternary structures ranging from the heterotrimeric organization of the eukaryotic RPA ( 29 ) to the dimeric and monomeric forms of several bacteriophage and viral SSB ( 15 , 30 ). An heterotrimer OB scaffold with four DNA-binding OB domains is present also in euryarchaea such Pyrococcus furiosus ( 31 ).…”
Section: Introductionmentioning
confidence: 99%
“…While the exact mechanism has yet to be conclusively elucidated, it is possible that this ssDNA binding protein may facilitate specific hybridization and protect ssDNA overhangs from endonuclease attack. 4,6 The simplicity of this modification makes it easy to use in place of the original formulation without any other modifications. Furthermore, by making this mix in-house with homemade Thermus thermophilus DNA Ligase, this mix can be made for less than $10 per milliliter, making it accessible in a wide variety of research settings.…”
Section: Resultsmentioning
confidence: 99%
“…4 Furthermore, SSB has been found to reduce secondary structure of ssDNA, improve PCR specificity, and improve the processivity of DNA polymerases. [5][6][7][8] Thus, we hypothesized that ET SSB would protect the ssDNA ends from cleavage and might additionally improve the efficiency and specificity of these ends annealing, resulting in a more accurate and efficient Gibson Assembly reaction (Enhanced Formulation, Figure 2b). Strikingly, this formulation, which we refer to as Enhanced Gibson Assembly, is significantly more accurate and efficient than the original formulation and is comparable to or better than a commercially available high-fidelity assembly mix.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, it has been reported that SSBs are also useful for the polymerase chain reaction (PCR) reaction to increase the specificity and amplification efficiency in a number of studies . Furthermore, SSBs involve in integration of metabolic pathways to help the enzymes to the location of binding‐sites and genome maintenance, which effectively finish the biotic processes of enzymes …”
Section: Introductionmentioning
confidence: 99%